2014
DOI: 10.4103/0974-9233.124093
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary implantation of scleral-fixated posterior chamber intraocular lenses in adult patients

Abstract: Purpose:The purpose of this study is to evaluate and to compare the results of primary and secondary scleral-fixated posterior chamber intraocular lens (PCIOL) implantations in adult patients.Materials and Methods:A retrospective analysis of scleral-fixated PCIOLs-implanted during (primary group) or after (secondary group) cataract surgery was performed. The median follow-up time of 96 patients was 6 months (minimum: 6; maximum: 35 months). Outcome measures were indications, corrected distance visual acuity (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 28 publications
3
43
0
6
Order By: Relevance
“…In both groups, a comparable refractive outcome by the biometry prediction error (1.1D in MFS vs. 1.4D in non-MFS) was found. This matches the median postoperative refractive error found by Yalniz-Akkaya et al in a study including 96 non-MFS eyes [23]. Contrarily, two other studies by Farrahi et al and Mutoh et al reported a much better mean refractive error of 0.56 D and 0.1D, respectively [24, 25] but were comprised of a smaller group of patients.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In both groups, a comparable refractive outcome by the biometry prediction error (1.1D in MFS vs. 1.4D in non-MFS) was found. This matches the median postoperative refractive error found by Yalniz-Akkaya et al in a study including 96 non-MFS eyes [23]. Contrarily, two other studies by Farrahi et al and Mutoh et al reported a much better mean refractive error of 0.56 D and 0.1D, respectively [24, 25] but were comprised of a smaller group of patients.…”
Section: Discussionsupporting
confidence: 86%
“…Taskapili et al reported a PME in 10% of eyes that underwent scleral lens fixation and Yalniz-Akkaya et al reported a PME in 6% for scleral lens fixation. Interestingly, Mutoh et al also found 0% PME following scleral IOL fixation [23, 25, 26]. Given the rates of PME in the literature, we expected a higher rate after scleral lens fixation because of the more invasive procedure for the eye.…”
Section: Discussionmentioning
confidence: 90%
“…Zonül ve kapsül zafiyeti olan olgularda en uygun GİL yerleştirilmesi zamanına ait literatür deprospektif randomize çalışma bulunmamaktadır. Ancak retrospektif olarak yapılan çalışmalarda, skleralfiksasyonluGİL'nin ilk seansta veya başka bir seansta yerleştirilmesinin görsel sonuçlar ve komplikasyon oranları açısından farklı olmadığı gösterilmiştir [24][25] . Bizim çalışmamızda da ameliyat sonrası görsel sonuçlar ve komplikasyonlar ayrı seanslarda skleral askılı GİL yerleştirilen çalışmalar ile farklı bulunmamıştır.…”
Section: Introductionunclassified
“…Çalışmamızda elde edilen EDGK sonuçları litaratür ile benzerlik göstermektedir 4,9,10,12,16 . Çalışmamızda ortalama EDGK'nın primer skleral ve iris fiksasyonlu grupta birbirine yakın iken; 0,5 ve üzerindeki EDGK'nın skleral fiksasyonlu grupta daha fazla olmasını iris fiksasyonlu gruptaki olgu sayısının azlığına bağladık.…”
unclassified